Experimental Investigation of the Dynamic Deformation of Wind Turbine Blades Based on 3D-Digital Image Correlation - Liru Zhang; Jing Jia; Shibing Shao; Wei Gao; Dachuan Niu (Energies, 2024)
A wind turbine is a rigid–flexible coupling system, and its blades will be deformed under the action of aerodynamic force, inertia force, and elastic force. To monitor the deformation of the blades, this paper builds a dynamic deformation measurement system for wind turbine blades based on 3D-DIC and directly measures the three-dimensional displacement distribution of different blades under different operating conditions to obtain the dynamic deformation of the blades. The experimental results show that the dynamic waving deformation of the blade shows the trend of increasing and then decreasing with the increase in wind turbine rotational speed and incoming wind speed, and when the rotational speed reaches 500 r/min and the incoming wind speed reaches 9 m/s, the blade deformation reaches the maximum value; the dynamic waving deformation of wind turbine blade decreases with the increase in the elastic modulus of the blade and the degree of the decrease decreases gradually; the dynamic deformation of is predicted by the multiple displacement distribution of different blades under different operating conditions, and is obtained by the fitting of the experimental data. This paper develops a 3D-DIC-based dynamic testing system for wind turbine blades, conducts experimental studies to verify and prove the practicality of the system, and finally obtains the prediction polynomials for the dynamic deformation of wind turbine blades under different operating conditions.